Innovation of Puter Ice Cream Tool for Business Productivity in Manggis Village: Inovasi Alat Es Krim Puter untuk Produktivitas Usaha di Desa Manggis - Fauzi, Muhammad Alvin; Mulyadi, Akhmad; Aisidah, Suffi Natul; Fatima, Siti; Haqewi, Muhammad Danil (International Consortium of Education and Culture Research Studies, 2025)
General Background: Small-scale food businesses in rural areas often face limitations in accessing affordable and energy-efficient production tools, hindering their growth and competitiveness. Specific Background: Traditional ice cream production methods typically rely on equipment that requires electricity or expensive machinery, making them less accessible to micro-enterprises in resource-limited settings. Knowledge Gap: There is a lack of simple, low-cost technological solutions tailored to the needs of small-scale producers seeking to improve efficiency without dependence on electrical power. Aims: This study aims to develop a hand-cranked ice cream maker using appropriate technology to support small business productivity, particularly in rural communities. Results: The device was designed and fabricated based on principles of simplicity, cost-efficiency, and manual operation. Performance testing revealed that the tool could produce ice cream within 15–20 minutes, delivering a product with taste and texture comparable to commercial ice cream. Novelty: The manually operated tool offers a sustainable and accessible alternative for small enterprises, enabling production without electricity while maintaining product quality. Implications: This innovation presents a viable solution for rural entrepreneurs by lowering production costs, reducing reliance on infrastructure, and promoting self-sufficiency. It contributes to the advancement of appropriate technology applications and supports the development of inclusive, grassroots-level economic opportunities in the culinary sector. Keywords: Appropriate Technology, Ice Cream Maker, Small Business, Manual Tool, Rural Innovation Highlights: Manual ice cream maker operates without electricity, ideal for rural use. Cost-effective design supports small-scale business productivity. Tool performance matches commercial product quality in short time.